2016
DOI: 10.1161/circulationaha.115.019983
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Workflow and Time to Treatment on Thrombectomy Outcome in the Endovascular Treatment for Small Core and Proximal Occlusion Ischemic Stroke (ESCAPE) Randomized, Controlled Trial

Abstract: Background— The Endovascular Treatment for Small Core and Proximal Occlusion Ischemic Stroke (ESCAPE) trial used innovative imaging and aggressive target time metrics to demonstrate the benefit of endovascular treatment in patients with acute ischemic stroke. We analyze the impact of time on clinical outcome and the effect of patient, hospital, and health system characteristics on workflow within the trial. Methods and Results— Relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
137
1
2

Year Published

2016
2016
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 227 publications
(148 citation statements)
references
References 30 publications
8
137
1
2
Order By: Relevance
“…Although the precise time when revascularization occurred in control arm cannot be determined, it is likely that higher rates of early revascularization in the intervention group compared with control group could explain this finding because longer onset to reperfusion time has been associated with a reduced likelihood of good outcome in most trials examining the clinical benefit of reperfusion (intravenous or endovascular). [14][15][16] Our results are similar to those observed in SWIFT PRIME where patients who achieved successful reperfusion at 27 hours had more favorable clinical outcome than those who did not reperfuse regardless of treatment allocation with a trend toward better outcomes in successfully reperfused patients in the intervention group compared with controls. 11 Importantly, REVASCAT has shown a strong association between the degree of revascularization and the probability to become functionally independent at 90 days (Figure 2).…”
Section: Extend-ia (Extending Time For Thrombolysis Insupporting
confidence: 83%
See 1 more Smart Citation
“…Although the precise time when revascularization occurred in control arm cannot be determined, it is likely that higher rates of early revascularization in the intervention group compared with control group could explain this finding because longer onset to reperfusion time has been associated with a reduced likelihood of good outcome in most trials examining the clinical benefit of reperfusion (intravenous or endovascular). [14][15][16] Our results are similar to those observed in SWIFT PRIME where patients who achieved successful reperfusion at 27 hours had more favorable clinical outcome than those who did not reperfuse regardless of treatment allocation with a trend toward better outcomes in successfully reperfused patients in the intervention group compared with controls. 11 Importantly, REVASCAT has shown a strong association between the degree of revascularization and the probability to become functionally independent at 90 days (Figure 2).…”
Section: Extend-ia (Extending Time For Thrombolysis Insupporting
confidence: 83%
“…The analysis of vessel revascularization at 24 hours followed this methodology, but associations between revascularization at 24 hours with infarct volume and functional outcome were analyzed post hoc. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]) at 24 hours and a higher rate of mortality (52.9% versus 13.8%) compared with those who did undergo follow-up imaging, and no significant differences were found regarding baseline clinical variables between the 2 groups.…”
Section: Methodsmentioning
confidence: 99%
“…6,7 The trial enrolled patients presenting within 12 hours from last seen healthy with disabling ischemic stroke, a small core infarct on noncontrast head CT (ASPECTS 6 -10), and moderate-to-good collaterals on CT angiography. 6,8 Because the 75th percentile for randomization to arterial access/groin puncture time was 28 minutes in the intervention group, patients randomized between 5.5 and 12 hours from last seen healthy (likely to undergo arterial access/groin puncture Ͼ6 hours from symptom onset/last seen healthy) were defined as the extended time window population for the current analyses.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have suggested that protective effects may be achieved using proximal flow control with a balloon guide catheter [8,9,10,11]. The ability of the stent retriever to retain the clot in the stent struts during clot retrieval is an important predictor of successful recanalization and may in part be affected by the device design.…”
Section: Introductionmentioning
confidence: 99%